The Effect of Broadband Internet on Mental Health-Related Disability Insurance Claims - Sofía Fernández Guerrico; Ilan Tojerow (Institute of Labor Economics (IZA), 2025)
We examine the causal impact of high-speed internet on adult mental health using administrative data from Belgium. We exploit predetermined telecommunications infrastructure and broadband technology's distance-sensitive nature for identification. Our difference-in-differences estimates show internet increased mental health-related disability insurance claims by 0.054 percentage points—a 31% increase relative to the control group. These findings are supported by increased antidepressant use at the municipality level. Results point to a work-related mechanism: effects are concentrated among knowledge workers and those in high work-from-home potential jobs. Time-use data show a substitution from leisure to work and less social interaction on weekends.
Keywords: H55; I1; J2; L86; 330; mental health; internet; disability insurance; employment